Characterization of the Therapeutic Effects of Novel Chimeric Antigen Receptor T Cells Targeting CD38 on Multiple Myeloma - Li, Xiaorui; Feng, Yaru; Shang, Fengqin; Yu, Zhuoying; Wang, Tieshan; Zhang, Jing; Song, Zhiru; Wang, Ping; Shi, Bingjie; Wang, Jianxun (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is a tumor type characterized by the unregulated proliferation of clonal plasma cells in the bone marrow. Immunotherapy based on chimeric antigen receptor T cell (CAR-T) therapy has achieved exciting success in the treatment of hematological malignant tumors. CD38 is highly and evenly expressed in MM and is an attractive target for MM treatment. Here, we successfully constructed two novel second-generation CAR-T cells targeting CD38 by retroviral vector transduction. CD38 CAR-T cells could be activated effectively after stimulation with CD38-positive tumor cells and secrete cytokines such as IFN-γ and TNF-α to promote tumor cell apoptosis in vitro experiments. Real-time fluorescence monitoring experiments, luciferase detection experiments and flow cytometry experiments revealed the efficient and specific killing abilities of CD38 CAR-T cells against CD38-positive tumor cells. The proliferation ability of CD38 CAR-T cells in vitro was higher than that of nontransduced T cells. Further antitumor experiments in vivo showed that CD38 CAR-T cells could be quickly activated to secrete IFN-γ and eliminate tumors. Thus, novel CD38-targeted second-generation CAR-T cells have efficient and specific antitumor activity and may become a novel therapy for the clinical treatment of MM.